How Slovene primary school pupils spend their summer holidays - Jurak, Gregor (Kinesiologia Slovenica, 2002)
The intention of the research was to analyse how Slovene primary school pupils spend their summer holidays. The analysis included 7344 Slovene primary school pupils and was based on a questionnaire completed by children at home. The data were analysed by means of the calculation of Pearson's 2 coefficient, Spearman's correlation coefficient and the discriminant analysis. It has been established that during the summer holidays the Slovene primary school pupils are more active as far as sport is concerned than a few years ago; as regards other aspects, they spend their summer holidays in a more healthy way, as well. Their organiyed and unorganiyed sports activities in this period of time are mostly affected by the sports activity of their parents. The analysis of sports activities the primary school pupils take part in during the summer holidays shows that they mostly engage in the following activities: cycling, swimming, playing football and roller skating. There are differences between the sexes, since boys prefer team sports, whereas girls prefer individual sports activities, in which there is less physical contact and which demand less muscular exertion. Pupils would like to take part in sports activities in the school gym during the summer holidays. We therefore propose a national project which would enable the use of school gyms during summer holidays.
Keywords: osnovne šole; poletne počitnice; prosti čas; športna dejavnost; učenci